UPAYA PENINGKATAN PRODUKTIVITAS SAPI LOKAL(SAPI JAWA-BREBES) MELALUI PENGUATAN PAKAN BERBASIS BAHAN BAKUPAKAN LOKAL DAN WAFER SUPLEMEN PAKAN - Iwan Prihantoro; Yuli Retnani; Taryati; Agustinus Tri Aryanto (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Brebes, 2018)
National livestock is still dominated by smallholder farmers. In some areas, cattle farmingis still in traditional way. Poor livestock management causes low livestock productivity under itsgenetic potential. It is necessary to find alternative feed for forage subsitusion in the dry season.Easy and cheap feed processing technology is needed to process by product into durable and easyto handle feed. One of feed processing product is wafer. The aim of this research was to identifythe source of raw material of local feed and its quality as wafer feed supplement for JawaBrebeslocal cattle. The research consists of several steps were identification of local raw materials inBrebes, wafer production of feed supplements based on local resource raw materials, physicalquality and nutrient test of wafer feed supplement and palatability test.Research of local rawmaterial identification in Brebes consists of local and domestic grass, and agriculture by productthat could be used as local resources which can increase added value. Wafer feed processingtechnology as feed supplements can improve the physical quality and nutrient raw materials oflocal resources.The raw materials used in wafer feed supplements were corn and gamal byproducts. Wafer feed supplement contain 14% moisture content,crude protein 30% and highpalatability for Jawa Brebes cattle.